1995
DOI: 10.1103/physrevc.52.r2839
|View full text |Cite
|
Sign up to set email alerts
|

Intruder bands inTe114: Smooth band termination

Abstract: The nucleus " Te has been studied in heavy-ion y-ray spectroscopy experiments performed with the early implementation of the GAMMASPHERE multidetector array. Three rotational intruder bands have been observed up to high spins. The yrast band, involving the 4p2h (h»/z) (g7/p) (g9/2) proton configuration, reaches I=48fi, at an excitation energy of 30.3 MeV, the highest observed spin connected by y rays in this mass region. The band properties are interpreted in the framework of smooth band termination.PACS numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…For 114 Te, quasicontinuum gamma-ray spectra from a fusion reaction suggest the presence of collective rotation in the high spin region I > ∼ 35h [11]. Rotational band structures were observed recently up to spin I ∼ 50h; the moment of inertia associated with the observed rotational bands decreases with spin, indicating that the collective rotation may terminate at the highest spins [12]. In the present calculation for 114 Te, we neglect the possibility of band termination and choose a fixed value for the deformation, for simplicity.…”
Section: Systematics and Varieties Of Rotational Dampingmentioning
confidence: 96%
“…For 114 Te, quasicontinuum gamma-ray spectra from a fusion reaction suggest the presence of collective rotation in the high spin region I > ∼ 35h [11]. Rotational band structures were observed recently up to spin I ∼ 50h; the moment of inertia associated with the observed rotational bands decreases with spin, indicating that the collective rotation may terminate at the highest spins [12]. In the present calculation for 114 Te, we neglect the possibility of band termination and choose a fixed value for the deformation, for simplicity.…”
Section: Systematics and Varieties Of Rotational Dampingmentioning
confidence: 96%
“…More recent discrete spectroscopy studies made with multigermanium detector arrays have identified discrete rotational bands at high spins for several nuclei in the A 110 120 mass region. We have chosen to study the nucleus 114 Te, for which three rotational bands have been observed [7], as a representative example in this mass region, using for the first time the same analysis technique developed for the study of rare-earth nuclei. Keeping the above picture in mind we focus mainly on a comparative analysis of the 114 Te nucleus with the rare-earth nucleus 164 Yb, which is stable in deformation and well studied by discrete line spectroscopy [8].…”
mentioning
confidence: 99%
“…The [21,4] − configuration (following the notation introduced by Afanasjev and Ragnarsson [25]) gives rise to a terminating spin of 95/2 − as a result of the aligning of the spins of all the particles and holes outside the core 100 Sn. The band needs to be studied up to spins higher than those observed in the present work (J π = 59/2 − ) or reported in the literature (75/2 − ) and lifetimes of such excited states have to be measured in order to arrive at a firm conclusion regarding band termination.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, rotational bands have been observed up to high spins in several Sn, Sb and Te isotopes [2][3][4]. Some of these bands have been interpreted in terms of configuration-dependent cranked Nilsson-Strutinsky calculations that predict a gradual change from collective prolate at low spin to non-collective oblate at high spin, leading to smooth band termination.…”
Section: Introductionmentioning
confidence: 98%